Antiseptic and Disinfectants, Their Use in Dentistry - Valijonovna, Orifkhujaeva Mekhriniso (Journal of Science in Medicine and Life, 2024)
Antiseptic agents are used to eliminate microorganisms located on the surface of the skin, mucous membranes, wound. They exert a bacteriostatic (stopping copulation) or bacteriocid (Salvation) effect on microorganisms and, due to this, prevent the infectious process, prevent it from developing, stop it. They also have a healing effect, as such means have a local effect, eliminating the hunger of infection. Some substances denature proteins in the protoplasm of microorganisms, that is, they exert a bacteriocid effect. Such means are called disinfectants-means.